Sustainable urban forms and communities: Urban geographies of eastern India - Sivaramakrishnan, Lakshmi; Bandyopadhyay, Sumana (London Routledge, 2025)
This volume discusses the patterns and trends of urbanization in West Bengal - one of the most urbanized states of India in the early part of the 20th Century. It focuses on the emerging urban landscapes of the state and neighbouring areas on building sustainable urban units and sustainable communities. The book explores the changing urban geographies of the emerging towns of the state and discusses how proper governance can help them to change into sustainable urban units. It presents the historical context of urbanization of West Bengal and traces the factors responsible for the urban primacy of the state. It discusses topics such as the development of the spatial patterns and urbanization, spatial trends of urban growth using remote sensing and GIS techniques, well-being and resilience in the urban society, impact of urbanization on the health status of its citizens, and decentralized governance for inclusive and sustainable development of cities. It also focuses on urban growth, land-use change and its impact on the urban environment. Based on empirical research, this book will be useful for students, teachers and researchers of geography, urban geography, urban studies, urban development and planning, regional planning urban sociology, politics, and urban economics. It will also be of interest to geographers, urban planners, community of geographers, professionals engaged in the discipline, and those interested in the urban geography of West Bengal and eastern India.
Keywords: Urbanization--India--West Bengal; Sustainable development--India--West Bengal; West Bengal (India)--Social conditions